Strategi Pengembangan Infrastruktur Di Kota Bogor - Bachtiar Sundasyah; Ruchyat Deni Djakapermana; Janthy Trisulianthy Hidayat (Syntax Idea)
Urban infrastructure development in the City of Bogor plays a crucial role in supporting sustainable development, in line with the Sustainable Development Goals (SDGs) 6, 9, and 11. This thesis examines urban infrastructure development strategies covering road networks, clean water, wastewater, and waste management. The focus of the study is on evaluating the performance of these infrastructure services and calculating their sustainability values using the Multi Dimensional Scaling (MDS) and Rapinfra methods. The research aims to formulate strategies that can improve the quality, reliability, and accessibility of infrastructure for all residents of Bogor City. The results of the study highlight the importance of an integrated and sustainable approach to urban infrastructure development to support economic growth, social welfare, and environmental preservation. The conclusion of this research emphasizes that infrastructure development strategies measured by environmental, economic, social, technological, and governance dimensions are essential and align with the goals of sustainable development